Transitioning from daytime to nighttime operations in military training has a temporary negative impact on dynamic balance and jump performance in U.S. Army Rangers. Issue 9 (September 2021) - Ritland, Bradley M.; Naylor, Jacob A.; Bessey, Alexxa F.; McKeon, Ashlee B.; Proctor, Susan P.; Capaldi, Vincent F.; Mantua, Janna; Sowden, Walter J.
Abstract: Objectives: Explore the impact transitioning from daytime to nighttime operations has on performance in U.S. Army Rangers. Methods: Fifty-four male Rangers (age 26.1 ± 4.0 years) completed the Y-Balance Test (YBT), a vertical jump assessment, and a grip strength test at three time points. Baseline testing occurred while the Rangers were on daytime operations; post-test occurred after the first night into the nighttime operation training (after full night of sleep loss), and follow-up testing occurred six days later (end of nighttime training). Results: On the YBT, performance was significantly worse at post-test compared to baseline during right posteromedial reach (104.1 ± 7.2 cm vs 106.5 ± 6.7 cm, p = .014), left posteromedial reach (105.4 ± 7.5 cm vs 108.5 ± 6.6 cm, p = .003), right composite score (274.8 ± 19.3 cm vs 279.7 ± 18.1 cm, p = .043), left composite score (277.9 ± 18.1 cm vs 283.3 ± 16.7 cm, p = .016), and leg asymmetry was significantly worse in the posterolateral direction (4.8 ± 4.0 cm vs 3.7 ± 3.1 cm, p = .030) and the anterior direction (5.0 ± 4.0 cm vs 3.6 ± 2.6 cm, p = .040). The average vertical jump height was significantly lower at post-test compared to baseline (20.6 ± 3.4 in vs 21.8 ± 3.0 in, p = .004). Baseline performance on YBT and vertical jump did not differ from follow-up. Conclusions: Army Rangers experienced an immediate, but temporary, drop in dynamic balance and vertical jump performance when transitioning from daytime to nighttime operations. When feasible, Rangers should consider adjusting their sleep cycles prior to anticipating nighttime operations in order to maintain their performance levels. Investigating strategies that may limit impairments during this transition is warranted.